2016
DOI: 10.1098/rspb.2016.0196
|View full text |Cite
|
Sign up to set email alerts
|

Facultative asexual reproduction and genetic diversity of populations in the humivorous termite Cavitermes tuberosus

Abstract: Termite colonies are typically founded by a pair of sexually reproducing dispersers, which can sometimes be replaced by some of their offspring. Some Reticulitermes and Embiratermes species routinely practice asexual queen succession (AQS): the queen is replaced by neotenic daughters produced by parthenogenesis, which mate with the primary king. Here, to cast light on the evolution of AQS, we investigated another candidate species, Cavitermes tuberosus (Termitinae). Of 95 nests, 39 contained a primary queen an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
67
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(73 citation statements)
references
References 44 publications
(69 reference statements)
6
67
0
Order By: Relevance
“…Therefore, it was astonishing that the mode of thelytoky in a higher termite, E. neotenicus, was found to be most like automixis with central fusion (Fougeyrollas et al, 2015). This is not the case for thelytoky of another higher termite, C. tuberosus, where parthenogens are completely homozygous, suggesting gamete duplication (Fournier et al, 2016). thelytokous parthenogenesis and eventually replace the old queens (Fig.…”
Section: Termite Parthenogenesismentioning
confidence: 95%
See 4 more Smart Citations
“…Therefore, it was astonishing that the mode of thelytoky in a higher termite, E. neotenicus, was found to be most like automixis with central fusion (Fougeyrollas et al, 2015). This is not the case for thelytoky of another higher termite, C. tuberosus, where parthenogens are completely homozygous, suggesting gamete duplication (Fournier et al, 2016). thelytokous parthenogenesis and eventually replace the old queens (Fig.…”
Section: Termite Parthenogenesismentioning
confidence: 95%
“…AQS was first identified in a lower termite species, R. speratus (Matsuura et al, 2009), and later confirmed in two other species of the same genus, R. virginicus (Vargo et al, 2012) and R. lucifugus (Luchetti et al, 2013), and was recently identified in two species of higher termite (Termitidae), E. neotenicus (Fougeyrollas et al, 2015) and C. tuberosus (Fournier et al, 2016) (Table 1).…”
Section: Termite Parthenogenesismentioning
confidence: 99%
See 3 more Smart Citations